Breaking the cycle: a pilot study on autonomous Digital CBTe for recurrent binge eating - Murphy, Rebecca; Khera, Charandeep; Osborne, Emma L. (Frontiers in Digital Health, 2025)
BackgroundOnly a minority of people with eating disorders receive evidence-based psychological treatment. This is especially true for those with recurrent binge eating because the shame that accompanies binge eating affects help seeking and there is a shortage of therapists to provide psychological treatments. Digital programme-led interventions have the potential to overcome both barriers.ObjectiveThis study examined the acceptability and effectiveness of a new digital programme-led intervention directly based on enhanced cognitive behaviour therapy (CBT-E), which is an empirically supported psychological treatment for eating disorders.MethodsOne hundred and ten adults with recurrent binge eating (self-reporting characteristics consistent with binge eating disorder, bulimia nervosa, and similar conditions) were recruited through an advertisement on the website of the UK's national eating disorder charity, Beat. The intervention, called Digital CBTe, comprised 12 sessions over 8–12 weeks delivered autonomously (i.e., without external support). Participants completed self-report outcome measures of eating disorder features and secondary impairment at baseline, post-intervention, and 6-month follow-up.ResultsMost participants identified as female, White, and were living in the United Kingdom. Most participants (85%) self-reported features that resembled binge eating disorder, and the rest self-reported features that resembled bulimia nervosa (8%) and atypical bulimia nervosa (7%). On average, participants reported that the onset of their eating disorder was more than twenty years ago. Sixty-three percent of the participants completed Digital CBTe (i.e., completed active treatment sessions). Those who completed all sessions and the post-intervention assessment (n = 55, 50%) reported significant decreases in binge eating, eating disorder psychopathology, and secondary impairment at post-intervention. These improvements were maintained at follow-up. Large effect sizes were observed for all these outcomes using a completer analysis and post-intervention data (d = 0.91–1.43). Significant improvements were also observed for all outcomes at post-intervention in the intent-to-treat analysis, with medium-to-large effect sizes.DiscussionA substantial proportion of those who completed Digital CBTe and the post-intervention assessment experienced marked improvements. This provides promising data to support the conduct of a fully powered trial to test the clinical and cost-effectiveness of autonomous Digital CBTe.